Jungles and forests - Twist, Clint (London : Gloucester Press, 1992)
Examines the climatic conditions in a rain forest and their effects on the variety of plant and animal life found there. Includes related projects. Suggested level: intermediate, junior secondary
Includes glossary and index
Primary
Keywords: Jungles; Forests and forestry; Forests and forestry